2021
DOI: 10.3847/1538-4357/abed49
|View full text |Cite
|
Sign up to set email alerts
|

Matching Globular Cluster Models to Observations

Abstract: As ancient, gravitationally bound stellar populations, globular clusters represent abundant, vibrant laboratories, characterized by high frequencies of dynamical interactions, coupled to complex stellar evolution. Using surface brightness and velocity dispersion profiles from the literature, we fit 59 Milky Way globular clusters to dynamical models from the CMC Cluster Catalog. Without performing any interpolation, and without any directed effort to fit any particular cluster, 26 globular clusters are well mat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 107 publications
(136 reference statements)
1
28
0
Order By: Relevance
“…In Rui et al (2021a), we presented a framework for comparing CMC models to observed clusters based on surface brightness and velocity dispersion profiles. As an application of this framework, we analyzed the CMC Cluster Catalog and identified best-fit models for dozens of GCs observed in the Milky Way (MW), including NGC 6397, which was examined in detail in this earlier study.…”
Section: Cluster Modelsmentioning
confidence: 99%
See 4 more Smart Citations
“…In Rui et al (2021a), we presented a framework for comparing CMC models to observed clusters based on surface brightness and velocity dispersion profiles. As an application of this framework, we analyzed the CMC Cluster Catalog and identified best-fit models for dozens of GCs observed in the Milky Way (MW), including NGC 6397, which was examined in detail in this earlier study.…”
Section: Cluster Modelsmentioning
confidence: 99%
“…As an application of this framework, we analyzed the CMC Cluster Catalog and identified best-fit models for dozens of GCs observed in the Milky Way (MW), including NGC 6397, which was examined in detail in this earlier study. We direct the reader to Rui et al (2021a) for a more detailed discussion of our scheme for identifying best-fit models for a given observed system.…”
Section: Cluster Modelsmentioning
confidence: 99%
See 3 more Smart Citations